1995
DOI: 10.1002/jnr.490410110
|View full text |Cite
|
Sign up to set email alerts
|

Oxystdrol (7β‐hydroxycholestesteryl‐3‐oleate) promotes serotonergic reinnervation in the lesioned rat spinal cord by reducing glial reaction

Abstract: In the present study, following previous experience with electrolytic lesion of the rat brain, and subsequent reduction of reactive gliosis with 7 beta-hydroxycholesterol derivatives (Bochelen et al.: Neuroscience 51:827-834, 1992), we have performed a hemisection of the spinal cord in adult rats and investigated the influence of 7 beta-hydroxycholesteryl-3-oleate (oxysterol) on the intensity of the astrocytic reaction and the axonal regeneration. We have shown here that local administration of liposomes conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
1
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 75 publications
1
20
1
1
Order By: Relevance
“…In this model, using local pharmacological therapy based on a cholesterol derivative, we demonstrated that the blockage of astrocytes reactivity yielded some axonal regeneration (Gimenez y Ribotta et al, 1995).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In this model, using local pharmacological therapy based on a cholesterol derivative, we demonstrated that the blockage of astrocytes reactivity yielded some axonal regeneration (Gimenez y Ribotta et al, 1995).…”
mentioning
confidence: 83%
“…We cannot exclude the existence of complex regulators at the level of transcription, which operate during CNS maturation, and for which GFAP could be a limiting factor. The in vivo model was that of the lateral hemisection of the spinal cord in adult mice, at a lower thoracic level, adapted from our previous rat model (Gimenez y Ribotta et al, 1995). Our objective was to monitor astrocyte reactivity in this model and to correlate it with that of axonal regeneration, as well as to correlate these anatomical data tentatively with functional parameters.…”
mentioning
confidence: 99%
“…The authors suggest a role of astroglia in estrogen regulation of synaptic plasticity and brain repair. Gimenez y Ribotta et al [79]demonstrate that, subsequent to rat spinal cord lesions, another sterol, 7β-hydroxycholesteryl-3-oleate, significantly reduces the GFAP level in reactive astrocytes. These observations coincided with the initiation of serotoninergic neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we investigated the in vivo counterpart of this interaction in adult mice after complete unilateral hemisection of the SC (17). Because all dorsal and ventral tracts are totally transected on one side of the cord, hemisection yields a permanent unilateral hindlimb functional deficit.…”
mentioning
confidence: 99%